Developing Innovative Work Behavior in Retail E-Commerce Workers: Investigating the Effects of High-Performance Work Systems and Other Mediating Variables - Said, Muhammad Farras; Ardiyanti, Niken (The Asian Journal of Technology Management (AJTM), 2024)
Abstract. The e-commerce industry is considered a key driver of the digital economy in Indonesia. Therefore, the progress and sustainability of companies in the e-commerce industry, particularly in e-commerce retail, are of great importance. Fostering innovative behavior among employees in e-commerce retail companies is crucial. Hence, this research investigates the influence of high-performance work systems (HPWS) on innovative work behavior (IWB) in employees, and how psychological capital (PsyCap) and work engagement mediate this relationship. This study utilizes covariance-based structural equation modeling (CB-SEM) to analyze direct and mediating effects on IWB. The research findings indicate that there is a simultaneous (t-value = 4.4) and separate mediating influence of PsyCap (t-value = 5.87) and Work Engagement (t-value = 3.67) on the relationship between HPWS and IWB. The direct impact of HPWS on IWB is also significant (t-value = 1.70). This study provides practical insights for management to cultivate innovative behavior among employees through recommended HPWS practices, and how individual factors may explain the effect of HPWS in cultivating IWB. Additionally, it offers an overview of the flow of influence from HPWS to IWB, which can provide further research opportunities in the IWB development field.  Keywords:  HPWS, IWB, PsyCap, Work Engagement, e-commerce